GWAS of thyroid stimulating hormone highlights pleiotropic effects and inverse association with thyroid cancer - Wei Zhou (Nature Portfolio, 2020)
Thyroid stimulating hormone (TSH) is critical for normal development and metabolism. Here, the authors conduct a GWAS and suggest protective effect of higher TSH on risk of thyroid cancer and goitre.